Black and blue : how African Americans judge the U.S. legal system - Gibson, James L., 1951-; Nelson, Michael J., 1986- (New York, NY : Oxford University Press, 2018)
It is not hyperbole to proclaim that a crisis of legal legitimacy exists in the relationships between African Americans & the law & legal authorities & institutions that govern them. However, this legitimacy deficit has largely been documented through anecdotal evidence & a steady drumbeat of journalistic reports, but not rigorous scientific research. We posit that both experiences & in-group identities are commanding because they influence the ways in which black people process information, & in particular, the ways in which blacks react to the symbols of legal authority. Based on two nationally-representative samples, this text ties together four dominant theories of public opinion: legitimacy theory, social identity theory, theories of adulthood political socialization & learning through experience, & information processing theories.
Previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 23, 2018).
Keywords: Discrimination in justice administration -- United States; Race discrimination -- Law and legislation -- United States; African Americans -- Civil rights; United States. -- Supreme Court; United States -- Race relations; Law; Laws of specific jurisdictions & specific areas of law